Analisis Pengembangan Karir Karyawan di PT Honest Financial Tecnologies - Azzahra Sartika Yanwar; Christian Wiradendi Wolor; Marsofiyati Marsofiyati (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2024)
Human resources (HR) is a productive team that works as the driving force of an organization, both in institutions and companies. They are a valuable asset, so they must be trained and developed. Human resources include providing training, recruitment, and employee career development. Employee career development is the process of identifying employee career capabilities and applying the right model to attain them. Career development will affect the performance of an employee because career development is a formal approach taken by the company to ensure employees in the company with suitable qualifications, abilities, and experience when needed. Employee career development refers to a company's efforts to guide, train, and develop employees for the progress of a company. Examples of employee career development include rewarding employees with performance improvement training and employee transfers. Over time, some employees' performance development can help, support, and facilitate the smooth running of organizational or business activities.